Level of Knowledge and Attitude of Kualanamu International Airport Employee About Basic Life Support - Angeline; Ahmad Yafiz Hasby; Meriza Martineta; Ferryan Sofyan (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2021)
All level of communities should be taught about basic life support especially for workers who related to giving first aid, one of them is the airport. Ideally, everyone knows the basic first aid techniques and takes regular training to ensure that the knowledge stays on. Basic life support is an effort made to maintain the life of someone who is in danger which can get worse or death if it’s not treated quickly. Basic life support in the first hour can reduce up to 85% of mortality.